2018
DOI: 10.1242/jeb.185975
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb position affects facultative bipedal locomotion in lizards

Abstract: Recent work indicates that bipedal posture in lizards is advantageous during obstacle negotiation. However, little is known about how bipedalism occurs beyond a lizard's acceleratory threshold. Furthermore, no study to date has examined the effects of forelimb position on the body center of mass (BCoM) in the context of bipedalism. This study quantified the frequency of bipedalism when sprinting with versus without an obstacle at 0.8 m from the start of a sprint. Forelimb positions were quantified during biped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We hypothesize that the disturbances from obstacles can be regarded as opportunities to enhance mobility in complex environments (Figure 1). Biological studies have demonstrated that animals (Kinsey and McBrayer, 2018; Kohlsdorf and Biewener, 2006; McInroe et al, 2016; Wilshin et al, 2017) can coordinate their appendages or body segments (Schiebel et al, 2019; Zhong et al, 2018) to adjust the timing and positions of environment engagement (Gart and Li, 2018; Gart et al, 2018; Li et al, 2015) to achieve effective locomotion. In analogy to the selected leg sequence timing in biological locomotors, Johnson and Koditschek (2013) demonstrated that with a human-programmed leg activation sequence, a hexapedal robot can jump up a vertical cliff by using its front legs to hook on the cliff edge while pushing its rear legs against the vertical surface.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the disturbances from obstacles can be regarded as opportunities to enhance mobility in complex environments (Figure 1). Biological studies have demonstrated that animals (Kinsey and McBrayer, 2018; Kohlsdorf and Biewener, 2006; McInroe et al, 2016; Wilshin et al, 2017) can coordinate their appendages or body segments (Schiebel et al, 2019; Zhong et al, 2018) to adjust the timing and positions of environment engagement (Gart and Li, 2018; Gart et al, 2018; Li et al, 2015) to achieve effective locomotion. In analogy to the selected leg sequence timing in biological locomotors, Johnson and Koditschek (2013) demonstrated that with a human-programmed leg activation sequence, a hexapedal robot can jump up a vertical cliff by using its front legs to hook on the cliff edge while pushing its rear legs against the vertical surface.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted in dinosaurs that tail preservation is notoriously poor, very rarely does a caudal vertebral series appear complete and intact (Hone, 2012). In exploring our dataset, not including the tail, we have demonstrated that caudal vertebrae are not essential for indicating a facultatively bipedal mode, though long tails are undoubtedly associated with a bipedal mode in lizards (Snyder, 1962;Kinsey & McBrayer, 2018). Testing the predictive capabilities of the indicators presented here in a wider extant sample, such as hindlimb element length with respect to body size, will help form future research directions before application to the lepidosaur fossil record.…”
Section: Discussionmentioning
confidence: 66%
“…Regarding the morphology of the forelimb across locomotor modes, any interpretations should be considered in line with studies into forelimb kinematics in facultative bipedality. Recently, it has been noted that forelimb positioning contributes significantly to stabilization of lizard bipedal locomotion (Kinsey & McBrayer, 2018). This is particularly interesting, given our observation of longer ulnae in larger facultative bipeds than their obligately quadrupedal counterparts.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation